The Role of the Wife as the Main Breadwinner for Household Harmony in Bagorejo Village, Gumukmas, Jember - Azizah, Umi Nur; Wulandari, Yunita (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This study aims to examine the roles of wivel as the primary breadwinners in the context of family harmony in Bagorejo Village, Gumukmas, Jember. Along with economic development and increasing family needs, many wives are taking over financial responsibilities in the household. The methodology used in this research is qualitative, with data collection through interviews and direct observations of wives who serve as breadwinners. The findings indicate that while working wives can improve the family's economic condition, this also brings new challenges, such as reduced time for household management and child care, as well as impacts on interpersonal relationships within the family. However, with proper management, the role of wives as breadwinners can positively contribute to family harmony, provided there is effective communication between husband and wife. This research is expected to provide insights into the dynamics of gender roles and the balance of responsibilities within families in the modern era.